2022
DOI: 10.15252/embj.2021109783
|View full text |Cite
|
Sign up to set email alerts
|

Spt5 histone binding activity preserves chromatin during transcription by RNA polymerase II

Abstract: Nucleosomes are disrupted transiently during eukaryotic transcription, yet the displaced histones must be retained and redeposited onto DNA, to preserve nucleosome density and associated histone modifications. Here, we show that the essential Spt5 processivity factor of RNA polymerase II (Pol II) plays a direct role in this process in budding yeast. Functional orthologues of eukaryotic Spt5 are present in archaea and bacteria, reflecting its universal role in RNA polymerase processivity. However, eukaryotic Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…FACT holds the histone hexamer with its main body and presumably tethers the dissociated distal H2A-H2B dimer through the Pob3 CTD ( 44 ), although the latter might be less efficient, as indicated by the loss of a single H2A-H2B dimer in vitro ( 45 ) and the faster H2A-H2B exchange over H3-H4 in vivo ( 46 , 47 ). We speculate that the tail domains of Spn1, Spt6, Elf1, Spt5, Rtf1, Leo1, and Ctr9 ( 32 , 48 ), which are not observed in the current structures, could interact with the detached FACT-histone intermediate to prevent its diffusion, for its efficient upstream transfer. Alternatively, the FACT-histone octamer complex can be transferred downstream (iii′).…”
Section: Discussionmentioning
confidence: 79%
“…FACT holds the histone hexamer with its main body and presumably tethers the dissociated distal H2A-H2B dimer through the Pob3 CTD ( 44 ), although the latter might be less efficient, as indicated by the loss of a single H2A-H2B dimer in vitro ( 45 ) and the faster H2A-H2B exchange over H3-H4 in vivo ( 46 , 47 ). We speculate that the tail domains of Spn1, Spt6, Elf1, Spt5, Rtf1, Leo1, and Ctr9 ( 32 , 48 ), which are not observed in the current structures, could interact with the detached FACT-histone intermediate to prevent its diffusion, for its efficient upstream transfer. Alternatively, the FACT-histone octamer complex can be transferred downstream (iii′).…”
Section: Discussionmentioning
confidence: 79%
“…Notably, a recent study in S. cerevisiae shows that Spt4 not only facilitates transcription through nucleosomal barriers but also regulates nucleosome positioning, although the mechanism is still unclear [ 110 ]. From an evolutionary perspective, SPT5 gains a negatively charged N-terminal region (SPT5N) that interacts with the H2A-H2B dimer and the H3-H4 tetramer [ 106 , 111 , 112 ]. This interaction was recently found to assist in the redeposition of nucleosomal histones and thus preserve chromatin during elongation [ 112 ].…”
Section: The Regulation Of Nucleosome Dynamics and Histone Marks By Spt5mentioning
confidence: 99%
“…From an evolutionary perspective, SPT5 gains a negatively charged N-terminal region (SPT5N) that interacts with the H2A-H2B dimer and the H3-H4 tetramer [ 106 , 111 , 112 ]. This interaction was recently found to assist in the redeposition of nucleosomal histones and thus preserve chromatin during elongation [ 112 ].…”
Section: The Regulation Of Nucleosome Dynamics and Histone Marks By Spt5mentioning
confidence: 99%
“…Supporting this idea, the induction of lineage of specific genes are defective in both Mcm2- (Xu et al, 2022). Furthermore, the N-terminus of Spt5 contains a conserved histone binding motif, and this binding is important for the recycling of parental H3 following gene transcription in budding yeast (Evrin et al, 2022). Currently, the fate of parental histones at different chromatin domains Xenopus and HeLa cells (Snyder et al, 2009;Yankulov et al, 1999), and Mcm2 and Mcm5 are required for Pol II-mediated transcription (Snyder et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that Mcm2, Pole3 and Pole4 are involved in recycling both parental H3.3 and H3.1 in mouse ES cells following DNA replication (Xu et al ., 2022). Furthermore, the N-terminus of Spt5 contains a conserved histone binding motif, and this binding is important for the recycling of parental H3 following gene transcription in budding yeast (Evrin et al, 2022). Currently, the fate of parental histones at different chromatin domains during mouse ES cell differentiation is largely unknown.…”
Section: Discussionmentioning
confidence: 99%